Podmiotowość prawnomiędzynarodowa korporacji międzynarodowych wyzwaniem dla systemu ochrony inwestycji zagranicznych - Kochowska, Ewelina (Studia Prawa Publicznego, 2019)
This paper analyzes two issues: the current state of international investment law as to the question of the subjectivity of transnational corporations and whether this question contributes to changes in the system of protection of foreign investments. Transnational corporations have already some relevant attributes of the subjects of international law, although all we can say is that their international legal personality is incomplete, functional, relative and not independent. International legal personality of transnational corporations cannot be presumed and if it is for the purpose of assigning liability for infringements of the rules of jus cogens, this will not prejudge the subjectivity in the ﬁ eld of the use of international investment law. If international legal subjectivity of a transnational corporation has been decided upon, the future of the already existing norms of international law regarding the protection of investments (including diplomatic protection, BIT provisions and multilateral international agreements) is not clear. In this system, the rights and obligations of states and transnational corporations are not balanced as this area of international law favours investors (and thus also transnational corporations). States and local communities are neither entitled to claim damages from the investor when such damages are caused by an investment or if they arise from violations of the vital interests of the local community, nor may they bring counterclaims against the complaint to arbitration tribunals. Common goals for the whole international community, for which the concept of international legal personality of transnational corporations could be developed, have not as yet been precisely articulated. Unlike it is the case of liability for the international law of jus cogens, there are no strong axiological reasons to develop this concept in international investment law.